Dilema Praktik Kantor Akuntan Publik: Pertautan antara Keberlangsungan Hidup dengan Kualitas Audit - Anggraini, Anggi Ratna (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
This research focuses on the dilemma of small Public Accounting Firms in maintaining their survival, but still maintaining their audit quality. This research is qualitative research with interpretive paradigm and the case study method. This study shows how Public Accounting Firm X faces a dilemma situation when auditing small clients with low fees, while maintaining their audit quality. Public Accounting Firm X in its survival growth strategy uses a